The role of elagolix in the suppression of ovulation in donor oocyte cycles - Catherine Boniface, M.D; Jessica N. Schnorr, M.D; Jeff Gray, Ph.D; Jessica McLaughlin, M.D; Heather Cook, M.D; Michael Slowey, M.D; John Schnorr, M.D (Elsevier, 2023)
Objective: To study the clinical use of elagolix in ovarian stimulation and its effect on premature ovulation in a cohort of women undergoing oocyte donation. Design: A prospective cohort study with the use of historical controls. Setting: A private reproductive endocrinology and infertility clinic. Patient(s): Seventy-five oocyte donors and 75 historical donors, aged 21-30 years, who had each passed Food and Drug Administration and American Society for Reproductive Medicine-approved oocyte donor screening. Intervention(s): Administration of elagolix 200 mg orally every night at bedtime with development of a follicular size of ≥14 mm for ovulation suppression compared with ganirelix 250 μg every night at bedtime. Main Outcome Measure(s): Premature ovulation rate, total oocytes, mature oocytes, maximum estradiol, luteinizing hormone, and progesterone levels. Result(s): Oocytes were available in all retrievals because there were no instances of premature ovulation in either the elagolix or ganirelix groups. There were no statistically significant differences between the groups in baseline demographics. Both groups had the same amounts of gonadotropins consumed and days of stimulation. The average number of total oocytes was similar between the control group and elagolix group (30.55 vs. 30.31). Furthermore, the average number of mature oocytes was similar between the control and study groups (25.42 vs. 24.73). An analysis of the 580 fresh oocytes in the elagolix group and the 737 fresh oocytes in the ganirelix group showed similar outcomes with fertilization rates of 79.7% and 84.6%, respectively. Blastocyst development rates were also similar: 62.9% in the elagolix group and 57.3% in the ganirelix group. Conclusion(s): Compared with a historical control group using ganirelix, patients receiving elagolix demonstrated a similar number of oocytes and mature oocytes with on average 4.2 fewer injections per cycle and average per-cycle patient savings of $289.10. Clinical Trial Registration Number: Western IRB Pr. No.: 20191163, April 11, 2019. First enrollment June 20, 2019.